Calidad nutricional in vitro de la moringa oleifera para La alimentación animal - Álvarez Aspiazu, Angie Anahí (2022)
The research was carried out at the Laboratory of Rumiology and Nutritional Metabolism "RUMEN", located at the "La María" Campus of the Quevedo State Technical University (UTEQ). The objective was to evaluate the effect of cutting age on the in vitro nutritional quality of Moringa oleifera leaves and stems.